Polyfunkční dům - Boudyšová, Helena (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Cílem diplomové práce je návrh polyfunkčního domu. Projektová dokumentace řeší čtyřpodlažní polyfunkční dům. Jedná se o samostatně stojící budovu. Stavba je řešena jako novostavba čtyřpodlažního, nepodsklepeného polyfunkčního domu. Konstrukční systém je navržen se systému POROTHERM. Stropní konstrukci tvoří předpjaté stropní panely SPIROLL. Střecha je pultová s krytinou z asfaltových pásů. Dům je založen na monolitických betonových základových pásech.

The aim of the Diploma Thesis is a multifuncional building design. The Design Documentation deals with a four-storey multifunctional building. This multifunctional building is separately standing building. The building is designed as a newly constructed four-storey multifuncional building, without basement. The strucural system is desinged in a walled technology of POROTHERM system. Ceilings are made of prestressed concrete ceiling panels. The roof is shed, made of asphalt felts. The house will be founded on monolithic concrete continuous footing strips.
Multi-functional building
Keywords: Polyfunkční dům Čtyřpodlažní Nepodsklepený Zděné stěny Předpjaté stropní panely Pultová střecha Základové pásy; Multifuncional building Four-storey With basement Masonry walls Prestressed concrete ceiling panels Shed roof Continuous footing strips